The use of international collaborative online learning methodology in a medical course – a learning experience - Laura Duque-Echeverri; Yuban Sebastián Cuartas-Agudelo; Miguel Eduardo Saavedra-Valencia; Santiago Castañeda-Palacio; Lina María Martínez-Sánchez (Revista Internacional de Educação e Saúde, 2023)
INTRODUCTION: The Collaborative Online International Learning (COIL) methodology uses a strategy called “Mirror classroom”, where two or more teachers and students from different teaching institutions can share a course through the use of technological tools. The rise of the COIL methodology increased due to the COVID-19 pandemic, once Higher Education Institutions had to develop support strategies in digital formats to give continuity to the academic mobility processes. OBJECTIVE: The objective of this article is to present the COIL strategy as a hybrid education method that facilitates learning and peer interaction in a class at the Faculty of Medicine of a University in Colombia. METHODOLOGY: For the realization of the collaborative experience, the students with their groups must carry out a bibliographical search in databases (PubMed, Science Direct, and Embase) related to the topic under discussion related to genes, nutrition, and obesity. Based on the information they compiled, they will have to create a creative infographic where they will expose the importance of genetic expression and its relationship to the obesity process. Finally, make a video exposing the results of the research carried out. CONCLUSION: The international collaborative work methodology is an educational strategy that allows the development of soft skills in students and teachers, and the development of teamwork skills, among many others. This type of education allows interpersonal relationships with people who have different locations worldwide.